2020
DOI: 10.3389/fcell.2020.00351
|View full text |Cite
|
Sign up to set email alerts
|

Friend or Foe? Recent Strategies to Target Myeloid Cells in Cancer

Abstract: The tumor microenvironment (TME) is a complex network of epithelial and stromal cells, wherein stromal components provide support to tumor cells during all stages of tumorigenesis. Among these stromal cell populations are myeloid cells, which are comprised mainly of tumor-associated macrophages (TAM), dendritic cells (DC), myeloid-derived suppressor cells (MDSC), and tumor-associated neutrophils (TAN). Myeloid cells play a major role in tumor growth through nurturing cancer stem cells by providing growth facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 217 publications
(246 reference statements)
2
40
0
1
Order By: Relevance
“…Many studies reported the importance of targeting MDSCs and GAMMs in glioma, given the highly immunosuppressive nature of these cells 60 - 62 . Various therapeutic approaches to target MDSCs in glioma have been developed with the aim to directly eliminate MDSCs or inhibiting the migration and expansion into the TME 63 . Many of these strategies consist in combination therapies using chemotherapeutic agents like TMZ and immunotherapy 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies reported the importance of targeting MDSCs and GAMMs in glioma, given the highly immunosuppressive nature of these cells 60 - 62 . Various therapeutic approaches to target MDSCs in glioma have been developed with the aim to directly eliminate MDSCs or inhibiting the migration and expansion into the TME 63 . Many of these strategies consist in combination therapies using chemotherapeutic agents like TMZ and immunotherapy 63 , 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Various therapeutic approaches to target MDSCs in glioma have been developed with the aim to directly eliminate MDSCs or inhibiting the migration and expansion into the TME 63 . Many of these strategies consist in combination therapies using chemotherapeutic agents like TMZ and immunotherapy 63 , 64 . However, the effect of TMZ on MDSCs has not been largely investigated, especially in patients, and further studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Under obesogenic conditions, the crosstalk between dysregulated adipose tissue, inflammatory mediators and tumor cells can have adverse impacts on BC outcomes ( 92 ). Autocrine and paracrine signaling mechanisms drive anti- and pro-inflammatory signals within the tumor microenvironment, linking inflammation to tumor aggressiveness, disease progression and chemoresistance programs ( 92 , 93 ).…”
Section: Mediators Of Inflammation and Immunosuppression In Obesity–bmentioning
confidence: 99%
“…Under obesogenic conditions, the crosstalk between dysregulated adipose tissue, inflammatory mediators and tumor cells can have adverse impacts on BC outcomes ( 92 ). Autocrine and paracrine signaling mechanisms drive anti- and pro-inflammatory signals within the tumor microenvironment, linking inflammation to tumor aggressiveness, disease progression and chemoresistance programs ( 92 , 93 ). This communication, which also includes other stromal components (i.e., fibroblasts and tumor-adjacent normal tissue), creates a milieu promoting genetic instability that enhances every aspect of BC progression from increasing proliferation, reducing apoptosis, and facilitating angiogenesis, migration, and ultimately metastasis ( 94 ).…”
Section: Mediators Of Inflammation and Immunosuppression In Obesity–bmentioning
confidence: 99%
“…The most direct MDSC-targeting therapy strategy is to eliminate MDSCs. Treatment with low doses of chemotherapy drugs, such as gemcitabine, 5-fluorouracil (5-FU), paclitaxel, and cisplatin, effectively affects the viability of MDSCs [8,28,105]. Gemcitabine is a selective inhibitor of MDSCs that reduces the number of circulating T regs and the level of TGFβ1 and PMN-MDSCs but not M-MDSCs in the peripheral blood of patients with pancreatic cancer and restores the proliferation and antitumor capacity of effector T cells [106].…”
Section: Depletion Of Mdscsmentioning
confidence: 99%